DOSE RESPONSE EFFECT OF Paracoccidioides brasiliensis IN AN EXPERIMENTAL MODEL OF ARTHRITIS - Loth, Eduardo Alexandre; Biazim, Samia Khalil; Santos, José Henrique Fermino Ferreira dos; Puccia, Rosana; Brancalhão, Rosimeire Costa; Chasco, Lucinéia de Fátima; Gandra, Rinaldo Ferreira; Simão, Rita de Cássia Garcia; Franco, Marcello Fabiano de (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Paracoccidioidomycosis (PCM) is caused by the dimorphic fungus Paracoccidioides brasiliensis (Pb) and corresponds to prevalent systemic mycosis in Latin America. The aim of the present work was to evaluate the dose response effect of the fungal yeast phase for the standardization of an experimental model of septic arthritis. The experiments were performed with groups of 14 rats that received doses of 103, 104 or 105 P. brasiliensis (Pb18) cells. The fungi were injected in 50 µL of phosphate-buffered saline (PBS) directly into the knee joints of the animals. The following parameters were analyzed in this work: the formation of swelling in knees infused with yeast cells and the radiological and anatomopathological alterations, besides antibody titer by ELISA. After 15 days of infection, signs of inflammation were evident. At 45 days, some features of damage and necrosis were observed in the articular cartilage. The systemic dissemination of the fungus was observed in 11% of the inoculated animals, and it was concluded that the experimental model is able to mimic articular PCM in humans and that the dose of 105 yeast cells can be used as standard in this model.